Highly efficient solar-driven photocatalytic hydrogen evolution by a ternary 3D ZnIn2S4–MoS2 microsphere/1D TiO2 nanobelt heterostructure. (22nd July 2021) - Zhou, Hanghang; Wang, Lan; Shi, Hang; Zhang, Huan; Wang, Yue; Bai, Shiqi; Yang, Yifan; Li, Yujuan; Zhang, Tingting; Zhang, Hongzhong
Abstract : Herein, a novel ternary three-dimensional (3D) ZnIn2 S4 –MoS2 microsphere/one-dimensional (1D) TiO2 nanobelt photocatalyst was created, achieving excellent photocatalytic H2 evolution performance under visible light irradiation. Abstract : Combining different semiconductor materials with diverse geometric structures and energy level configurations is an effective strategy for constructing heterostructured photocatalysts with high activity. Using a solvothermal method, 1D TiO2 nanobelts were uniformly embedded into the gaps of flower-like 3D ZIS/MoS2 microspheres to allow atomic interactions. Therefore, a 3D ZnIn2 S4 –MoS2 microsphere/1D TiO2 nanobelt (ZIS/MoS2 /TiO2 ) composite with outstanding hydrogen production performance was synthesized. The unique heterostructure had a favorable energy level distribution and spatial structure, which could improve the interfacial charge transfer. Upon optimizing the weight ratios of the components, the maximum photocatalytic H2 evolution rate was 8440.28 μmol g −1 h −1 when using the 250%-ZIS/25%-MoS2 /TiO2 composite under simulated sunlight irradiation, which was ∼44.4 and 2181.0 times higher than when using pure ZIS and TiO2, respectively. In addition, apparent quantum efficiency (AQE) values of 39.33% at 380 nm and 30% at 420 nm were achieved. Importantly, the hydrogen production rate was 94.1% of the initial rate after four cycles, showing excellent stability. The photocatalytic hydrogen evolution mechanism of the prepared photocatalyst was also discussed in detail.